Micro-homogeneity evaluation of a bovine kidney candidate reference material - Liliana Castro; Edson Gonçalves Moreira; Marina Beatriz Agostini Vasconcellos (Brazilian Journal of Radiation Sciences)
The minimum sample intake for which a reference material remains homogeneous is one of the parameters that must be estimated in the homogeneity assessment study of reference materials. In this work, Instrumental Neutron Activation Analysis was used to evaluate this quantity in a bovine kidney candidate reference material. The mass fractions of 9 inorganic constituents were determined in subsamples between 1 and 2 mg in order to estimate the relative homogeneity factor (HE) and the minimum sample mass to achieve 5% and 10% precision on a 95% confidence level. Results obtained for HE in all the analyzed elements were satisfactory. The estimated minimum sample intake was between 2 mg and 40 mg, depending on the element.